Small unmanned aerial vehicles with line of sight in the company fire support team - Brantley, Jason (My University, 2026)
Nations have attempted to use Unmanned Aerial Vehicles (UAVs) on the battlefield since at least the First World War (Imperial War Museum, n.d.). However, the Russia-Ukraine War was the first war that saw widespread usage of the broad range of technologies that fall under the title Unmanned Aerial Systems (UAS). Both sides have used sophisticated multi-layered Unmanned Aerial Systems to engage targets with direct and indirect fires (CNA, 2023). It is undeniable that UAVs have significantly impacted the war, and other nations, including the United States, have become painfully aware that they are behind the curve in integrating UAS into every level of their militaries. Given the widespread usage of UAS in modern large-scale combat operations to detect artillery targets and increase fire mission processing speeds, the United States Army should integrate small UAVs (sUAVs) into company Fire Support Teams to increase their effectiveness in order to defeat near-peer adversaries. While the impact of UAVs is undeniable, it is still unknown exactly how much they improve the effectiveness of company-level Fire Support Teams. Since artillery is such a core element of the Russian Way of War, artillery units were early adopters of UAVs in the Russia-Ukraine War (Cranny-Evans, 2023). The advantage of being able to observe targets far forward of the front line without needing to put troops within eyesight of the target is immense. Still, it is unknown exactly how much more effective these units are with UAVs. The purpose of this research would be to determine what improvements are made in the key performance indicators of a Company Fire Support Team when a small UAS is integrated into its operations. The key performance indicators to be measured are observable area, target detection, and fire mission processing. A quantitative study with an experimental between-participant posttest-only control-group design was conducted to test these indicators. Eight Forward Observer teams composed of Kansas State University Reserve Training Officer Corps (ROTC) Cadets were separated into two groups. The control group was given basic fire support tools and occupied an observation post (OP). From that OP, each team had 10 minutes to identify as many targets as possible and process fire missions on them while maintaining Line of Sight with the UAV and the targets. Data on the key performance indicators were then compared to the data collected from the experiment group. The experiment group performed the same operation as the control group; except they were provided with a small UAV. Once the data was collected and analyzed, it was possible to begin to determine exactly how much the effectiveness of a company fire support team increased when a small UAV was integrated into its operations. This research did not examine the following factors: how the generated fire missions would be handled at the battalion level or above, the effects of large UAVs on the battlefield, how the current EW domain would affect the UAVs in question, or how fires planning would be affected by the introduction of UAVs at the company level.
Keywords: UAS; Fire support; Artillery; Drone; Army; Unmanned Aerial Vehicles